2020
DOI: 10.1007/s12178-020-09670-8
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Infection After Reverse Shoulder Arthroplasty: a Review

Abstract: Purpose of Review Periprosthetic infection is a relatively rare but potentially devastating complication after shoulder arthroplasty. The purpose of this article is to review the incidence, diagnosis, prevention, and management of periprosthetic infections after reverse shoulder arthroplasty, with a focus on literature published within the last 5 years. Recent Findings The 2018 International Consensus Meeting on Musculoskeletal Infection provides us with a framework for the diagnosis and management of peripros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…Numerous prior studies have indicated male gender and younger age as risk factors for subsequent PJI after TSA and RSA. 4 , 6 , 13 , 14 , 16 , 20 In the present study, male gender, younger age, and CCI were significant risk factors in multivariate analysis of the RSA cohort. Analysis of the TSA cohort showed male gender and younger age to be significant factors on univariate analysis; however, only younger age remained significant on multivariate analysis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Numerous prior studies have indicated male gender and younger age as risk factors for subsequent PJI after TSA and RSA. 4 , 6 , 13 , 14 , 16 , 20 In the present study, male gender, younger age, and CCI were significant risk factors in multivariate analysis of the RSA cohort. Analysis of the TSA cohort showed male gender and younger age to be significant factors on univariate analysis; however, only younger age remained significant on multivariate analysis.…”
Section: Discussionsupporting
confidence: 52%
“…Despite continuous advancements in techniques and technology for each of these procedures, periprosthetic joint infections (PJIs) continue to plague patients at a reported rate ranging from 0.5% to 5.0%. 4 , 11 , 13 , 14 , 15 , 16 , 20 , 24 The consequences of PJI are devastating for patients and represent a significant economic burden for our healthcare system. 15 , 20 , 23 Several studies have identified risk factors associated with PJI in TSA and RSA.…”
mentioning
confidence: 99%
“… 28 Factors that might explain the higher rate of RSA infection are increased implant surface, large subacromial dead space caused by the ball-and-socket configuration, common postoperative haematoma, extensive surgical dissection, patients with compromised general health and numerous previous procedures. 4 , 29 …”
Section: Infectionmentioning
confidence: 99%
“… 48 Currently recommended routine workup of shoulder prosthetic joint infection is similar to other artificial joints and includes plain radiographs, a basic set of labs including serum white blood cell count, C-reactive protein (CRP), and, most importantly, arthrocentesis with synovial fluid cell count and microbiology. 29 , 49 Because the cell count (in addition to histology) is dependent on the virulence of the causative organism, a lower threshold for diagnosis of shoulder prosthetic joint infection is expected due to the greater proportion of low-virulence organisms (e.g. Cutibacterium acnes).…”
Section: Infectionmentioning
confidence: 99%
“…So far, there are no clear diagnostic criteria that can diagnose all chronic PJIs. 10 In particular, chronic PJI caused by some less virulent bacteria is often more difficult to be diagnosed, which affects the choice of treatments. 11 Besides, there is no accurate detection method that can be used as the gold standard in relevant fields.…”
Section: Introductionmentioning
confidence: 99%